FLicKeR [videorecording (DVD)] - Sheehan, Nik (Altered consciousness collection, 2008)
Explores the life of Brion Gysin, inventor of a hypnotic light device called the Dreammachine, which was intended to induce hallucinations and transform consciousness. Includes interviews from some of the '60s counter-culture's most eccentric icons.